Kritik Praktik Materialistik Perspektif Al-Qur’an: Hermeneutika Makna Cum Maghza atas QS. Muhammad Ayat 36 - Nadhifatul Fuadah; Luthviyah Romziana (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the phenomenon of the strengthening of materialistic orientation in modern life, which not only affects economic and social aspects but also contributes to a crisis of human spiritual awareness. So far, the Qur'anic critique of worldly life has often been understood normatively as an affirmation of its transience, without being deeply connected to the structure of contemporary materialistic consciousness. A life orientation increasingly centered on material possession has shifted the meaning of life from spiritual values toward worldly achievements. This research aims to analyze QS. Muhammad: 36 using the Ma’na Cum Maghza approach to uncover its historical meaning while developing its dynamic significance in the modern context. This study employs a qualitative method with a library research design, using textual and contextual analysis of Qur'anic verses. The findings indicate that the concepts of la'ib and lahw in QS. Muhammad: 36 not only describe the temporality of worldly life but also represent a form of existential negligence when worldly life becomes the primary orientation. Excessive attachment to material possessions has the potential to create moral disorientation and weaken spiritual awareness. This study contributes to the development of contextual Qur'anic interpretation by offering a critical perspective on modern materialism and reaffirming the relevance of Qur'anic values in addressing contemporary social problems.